A Comprehensive Study on the Impact of Data Analytics in Ed-Tech - Gupta, Aditi (Digital Repository of Theses, 2024)
This comprehensive study investigates the impact of data analytics in the Educational Technology (EdTech) industry, examining its role in personalizing learning experiences, enhancing student retention, and refining educational strategies. The study performed semi-structured interviews with educators, students, and EdTech developers using an interpretive qualitative research approach. Using a purposeful sample of people with substantial experience in the EdTech ecosystem, these interviews attempted to collect a range of viewpoints on the application of data analytics in education. Key findings reveal that “data analytics plays” a transformative role in the EdTech industry. It significantly contributes to the customization of educational experiences, with tools such as adaptive assessments and real-time personalization enhancing student engagement and academic performance. Predictive analytics has been pivotal in identifying at-risk students, leading to improved retention rates. However, the reliance on data-driven interventions has raised concerns about privacy and the devaluation of qualitative insights. The study also finds that data analytics informs teaching strategies and resource allocation, aiding educators in optimizing educational resources. In the realm of EdTech development, data analytics feedback has spurred innovation, though challenges like potential biases and data management persist. Ethical considerations, particularly data privacy, emerged as a critical theme across all areas. The implications of the study are multifaceted, extending to educational practices, technology development, policy-making, and ethical considerations. Recommendations include adopting professional development in data analytics, implementing early intervention programs, designing EdTech solutions with privacy in mind, and updating educational data regulations. The study affirms the significant role of data analytics in enhancing the EdTech industry. While it brings substantial benefits in personalizing education and aiding educators, it also necessitates a balanced approach that integrates ethical practices. The study advocates for collaborative efforts to establish robust data governance frameworks and emphasizes the importance of continuous professional development and data literacy to ensure equitable and conscientious use of data analytics in education.